RESPON SISWA DALAM PEMBELAJARAN ONLINE SELAMA PANDEMI COVID-19 DI SMP NEGERI 1 DUMAI - Syafi'i, Muhammad; Rama Apri Wiranti, Wan; Yusnawati (PGRI Provinsi Riau, 2021)
The rapid spread of Covid-19 has disrupted several aspects of life, especially in the field of education. In order to inhibit the spread of Covid-19, schools are prohibited from conducting face-to-face learning processes in educational units so that learning activities are carried out at home through online learning. The purpose of this study was to see student responses related to learning achievements and online learning assessments during the Covid-19 pandemic at Junior High School 1 Dumai. The research was conducted at Junior High School on October 5 - December 15, 2020. The research method used was a survey. The instrument used is a questionnaire using gogogleform. The results of this study indicate that online learning is considered more difficult for students to understand and related to online learning assessment 43.8% of students like online learning provided by the teacher, 37.5% are ordinary and only 18.8% do not agree with the online learning provided. teacher. The causes of student difficulties in online learning can be caused by several things, including the varied learning styles of children. Students who have an auditory learning style, a model in which a person absorbs information more quickly through what they listen to, find it difficult to learn online, as well as students who have a kinesthetic learning style, students who absorb information through various physical movements. Another obstacle is the slow internet signal and the cost of the quota that must be provided for online learning. Â Â